Natural and semisynthetic substances with antitubulin activity - D, Guénard (Malaysian Journal of Science, 2000)
The tubulin test, a powerful tool to detect anticancer agents, was outlined briefly. Three classes of compounds, defined by their sites of fixation and their mechanisms of action were discussed.